Youth Help-Seeking Intention During the Covid-19 Pandemic: Comparison of Infection Rate in Living Area - Aprezo Pardodi Maba (Kuras Institute, 2022)
The aim of this study was to compare help-seeking intentions among youth living in areas with different Covid-19 infection rates during the pandemic. Data was collected using demographical questions and the General Help-seeking Questionnaire from a sample of 1,340 adolescents (971 females, 369 males) between August 11th and 21st, 2020. Of these participants, 423 (122 females, 301 males) were eligible for analysis. The data were analyzed using descriptive analysis and ANOVA. The results showed that youth living in areas with low Covid-19 infection rates had higher help-seeking intentions than those living in areas with high infection rates or no Covid-19 cases. These findings suggest that the rate of Covid-19 infection in an individual's living area may impact their help-seeking intentions during the pandemic. Further research is needed to fully understand the factors that contribute to help-seeking intentions during times of crisis and to develop interventions to support individuals in need of help. It is also important to consider the potential impact of other factors, such as access to resources and support systems, on help-seeking intentions among youth.